2014
DOI: 10.1002/glia.22668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astrocyte‐targeted production of interleukin‐6 in the mouse on the host response to nerve injury

Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine with a key role in the control of inflammatory/immune responses. In the central nervous system (CNS), an increase in IL-6 occurs in a wide range of pathological conditions such as excitotoxicity and traumatic brain injury. We evaluated the effects of astrocyte-targeted production of IL-6 in the CNS in the sterile-nerve injury model of facial nerve axotomy. To accomplish this, facial nerve transection was performed in transgenic mice (glial fibrillary acidic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 101 publications
5
36
0
1
Order By: Relevance
“…Our observations revealed that in comparison with control WT where Iba1 immunoreactivity in the mCC was very low (Fig. Qualitatively, we found that there is an increased number of Iba1 1 cells in the GFAP-IL6Tg compared with WT mice in agreement with other studies (Almolda et al, 2014). 6E,I).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our observations revealed that in comparison with control WT where Iba1 immunoreactivity in the mCC was very low (Fig. Qualitatively, we found that there is an increased number of Iba1 1 cells in the GFAP-IL6Tg compared with WT mice in agreement with other studies (Almolda et al, 2014). 6E,I).…”
Section: Resultssupporting
confidence: 93%
“…The AI index was calculated by multiplying the percentage of the stained area by the MGVM, as already published (Almolda et al, 2014). Analysis was performed on 2-3 sections from each animal.…”
Section: Densitometric Analysis and Cell Countingmentioning
confidence: 99%
“…It has been demonstrated that the expression of IL-6 in astrocytes is significantly increased during inflammation, neurodegenerative disease and in other pathological conditions (Almolda et al, 2014;Chlodzinska et al, 2011;Erta et al, 2012;Jankord et al, 2010;Spooren et al, 2011). During infection and especially after LPS injections, IL-6 synthesis is induced in microglia.…”
Section: Il-6 In Stress Responsesmentioning
confidence: 96%
“…By means of analySIS Ò software, both the percentage of area occupied by the immunolabelling as well as the intensity of the immunoreaction (Mean Grey Value Mean) was recorded for each photograph. For each marker, the AI index (Almolda et al, 2014) was calculated by multiplying the percentage of the immunolabelled area by the Mean Grey Value Mean.…”
Section: Densitometric Analysismentioning
confidence: 99%